Design of the synthetic-X control chart - Lee, Jeffrey Jiankai. (2012)
The Xbar chart is widely used to monitor the mean of a quality characteristic xbar. This chart decides the process status based on the magnitude of the sample mean xbar and is effective for detecting large mean shifts. The Exponentially Weighted Moving-Average (EWMA) control chart is another control chart used to detect the occurrence of a shift in a process mean and is effective for detecting small mean shifts. This report proposes the Synthetic-Xbar chart. The results of the performance studies show that Synthetic-Xbar chart always outperforms the Xbar chart and is easier to design and operate as compared to the EWMA chart.